THE EFFECT OF MONOPOLY POWER AND INTEGRITY ON THE TENDENCY TO COMMIT FRAUD IN E-PROCUREMENT - Hadi Avianto; Moh. Nizarul Alim; Tarjo Tarjo (Asia Pacific Fraud Journal, 2019)
The main objective of this study is to examine the influence of Monopoly Power and Integrity on fraud that occurs in the e-procurement process. This study involved parties directly related to the procurement of goods and services and the development of electronic procurement systems incorporated in the Procurement Service Unit (referred to in Indonesia as Unit Layanan Pengadaan / ULP) and the Electronic Procurement Services (or referred to Layanan Pengadaan Secara Elektronik / LPSE). This study used a quantitative approach and primary data in the form of questionnaire as measurement instrument. The method of analysis was done using SmartPLS 3. Path analysis and bootstrapping technique were used to test the hypothesis. The results of this study show that power monopoly has a significant positive effect on fraud in e-procurement, while integrity has a significant negative effect on fraud in e-procurement.